2019
DOI: 10.4081/cp.2019.1161
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Non-Atopic Dermatitis with Polarized UV-Free Polychromatic Light: A Case Report

Abstract: Non-atopic dermatitis is a common inflammatory condition, which is potentially debilitating and can compromise life quality. Polarized ultraviolet-free polychromatic light is used as therapeutic option for the treatment of wound healing and dermatological conditions. It has not yet been tested in the management of non-atopic dermatitis. In this case report, we present a 67-year-old female patient who had suffered with moderate non-atopic dermatitis for the past 20 years, and had undergone multiple treatments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The findings of this investigation supported those of Leguina-Ruzzi et al [18] , who assessed the efficiency of polarized light therapy in a patient with non-atopic dermatitis (NAD). Results showed that light treatment effectively decreased pruritis and skin dryness without any negative side effects or pain.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this investigation supported those of Leguina-Ruzzi et al [18] , who assessed the efficiency of polarized light therapy in a patient with non-atopic dermatitis (NAD). Results showed that light treatment effectively decreased pruritis and skin dryness without any negative side effects or pain.…”
Section: Discussionsupporting
confidence: 89%